Customers’ Loyalty and Sales Performance of Dangote Cement Product in Awka, Anambra State - Nosike, Chukwunonso; Egbunike, Chinedu (Annals of Management and Organization Research, 2021)
Purpose: The broad objective of the study is to ascertain the relationship between customers’ loyalty and the sales performance of Dangote Cement products in Awka, Anambra State. The study specifically examined the relationship between emotional loyalty and consumer purchase intention; and, the relationship between behavioral loyalty and consumer purchase intention of Dangote cement. Research methodology: The study adopts the survey research design. The final sample comprised one hundred and twenty-four (124) consumers of Dangote cement products in the Awka metropolis. The study relied on primary data; obtained from a structured questionnaire. The data were analyzed using descriptive statistics and the hypotheses were tested using the Pearson correlation coefficient. Results: The results showed a positive significant relationship between emotional loyalty and consumer purchase intention; and, a positive significant relationship between behavioral loyalty and consumer purchase intention. Limitations: The study focused on consumers of a single product, which limits the generalizability of the study findings to other different products. Contribution: The study contributes to the management discipline by understanding how customer loyalty impacts the continued purchase of an organization’s product or service. More so, the appeal now of using emotional marketing tools seems to be gaining increased popularity. The study also buttresses the fact that the consumers may be viewed from both a relational and transactional perspective.